Communicating Gender in Javanese Wayang Wong: A Semiotic and Historical Analysis of Cross-Gender Performance - Alan Munandar; Nabhan Fuad Choiron (Universitas Lambung Mangkurat, 2026)
This article examines how gender is constructed, communicated, and historically transformed in Javanese wayang wong through a network of simultaneous semiotic channels. The communication phenomenon at the center of the study is the persistence of cross-gender performance in a traditional theatrical form whose meanings are shaped not only by bodily signs, costume, vocality, and spatial arrangement, but also by Javanese cosmology and changing political contexts. Using a qualitative design based on documentary research and textual analysis, the study draws on ethnographic studies, historical accounts, performance documentation, and heritage records related to wayang wong in Central Java. The analysis combines theatre semiotics, gender performativity theory, and postcolonial historical interpretation, with data organized through movement, costume, vocal, spatial, and contextual sign systems. The findings show that gender in wayang wong is communicated as an embodied cultural language rather than a fixed biological category, and that the alus/kasar cosmological framework is more decisive than the female/male binary in organizing meaning. Practically, the study supports more contextual interpretation, preservation, and performance pedagogy in traditional arts. Its limitation lies in the reliance on documentary rather than field-based audience data, while its originality lies in positioning cross-gender performance as a historically dynamic communication system grounded in local cosmology rather than merely as theatrical role reversal.